Teaching subjectivity, intersectionality, and personal politics with Audre Lorde’s Zami - Katy Hull (Radical Teacher, 2023)
Keywords: afro-féminisme; amériques; approches et analyses; intersectionnalité; pédagogie; ressource en ligne; régions géographiques; thématiques; états-unis

Boite à outil. Approche par résultats, ADS+, Approche participative - Centre de formation communautaire de la Mauricie (CFCM); Centre de recherche sociale appliquée (CSRA); Table de concertation du mouvement des femmes de la Mauricie (TCMFM); Consortium de développement social de la Mauricie (Centre de formation communautaire de la Mauricie (CFCM)/Centre de recherche sociale appliquée (CSRA)/Table de concertation du mouvement des femmes de la Mauricie (TCMFM)/Consortium de développement social de la Mauricie, 2022)
« Ce document présente différents outils pour développer un projet concerté dans un approche ADS+. Il est particulièrement pertinent pour les urbanistes souhaitant adopter des perspectives participatives » [Résumé équipe ORPCC]
Keywords: 2000 à aujourd'hui; EDI; amériques; approches et analyses; intersectionnalité; orpcc; outils; pour des recherches en milieux de pratiques; pédagogie; périodes historiques; ressource en ligne; régions géographiques; thématiques

L’intersectionnalité - Université du Québec en Abitibi-Témiscamingue (2020)
L’intersectionnalité
Keywords: approches et analyses; cours; intersectionnalité; pol5480; premier cycle; pédagogie; ressource en ligne; thématiques

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Promouvoir des programmes d'éducation à la sexualité positive, inclusive et émancipatrice: méta-analyse qualitative intersectionnelle des besoins exprimés par les jeunes - Descheneaux, Julie; Fédération du Québec pour le Planning des naissances; Pagé, Geneviève; Piazzesi, Chiara; Pirotte, Magaly (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; approches et analyses; discipline; intersectionnalité; pratiques féministes; pédagogie; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; santé sexuelle; thématiques; éducation

La pédagogie féministe intersectionnelle socioconstructiviste de Relais-femmes dans son travail d’accompagnement-formation: des compétences à développer - Lafortune, Louise; Gervais, Lise; Lacharité, Berthe; Maheu, Josiane; St-Cerny, Anne; Guberman, Nancy; Coenga-Oliveira, Danielle; Anctil Avoine, Priscyll (Recherches féministes, 2018)
Les auteures présentent les résultats d’une recherche réalisée en 2016-2017 par l’équipe de Relais-femmes (RF) et la chercheuse Louise Lafortune. Leurs objectifs consistaient à clarifier le sens d’une pédagogie féministe intersectionnelle socioconstructiviste (FIS) dans le travail d’accompagnement-formation de RF auprès des groupes communautaires et de femmes et à préciser les compétences pour mettre en œuvre ce type de pédagogie. Le contexte théorique aborde les concepts de féminisme intersectionnel, de socioconstructivisme, d’accompagnement-formation et de compétences. Les données recueillies à l’occasion d’une recherche collaborative sont issues d’entrevues interactives fondées sur une approche féministe et le référentiel de compétences de Lafortune publié en 2015. Les résultats obtenus comportent six énoncés de compétences et des éléments à prendre en considération dans une définition éventuelle d’une pédagogie FIS pour contribuer au débat actuel sur le sujet. Une perspective de recherche à envisager serait de revoir certains accompagnements-formations de RF, d’en critiquer les aspects intersectionnels présents ou manquants et de compléter la recherche par une analyse de cas.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; accompagnement-formation; approches et analyses; intersectionnalité; pédagogie; périodes historiques; relais-femmes; ressource en ligne; thématiques

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences

Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

Le positionnement intersectionnel comme pratique de recherche: faire avec les dynamiques de pouvoir entre femmes - Marcillat, Audrey; Miramond, Estelle; Rupert, Nouri; Çıngı Kocadost, Fatma (Les cahiers du CEDREF, 2017)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; intersectionnalité; inégalités; militance; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

Navigating gender and sexuality in the classroom: Narrative insights from students and educators - McEntarfer, Heather Killelea (Routledge, 2016)
Gender identity and sexuality play crucial roles in the educational experiences of students, parents, and teachers. Teacher education must more directly address the ways that schools reflect and reproduce oppressive gender norms, working to combat homophobia, transphobia, heteronormativity, and gendered expectations in schools. This volume examines teacher candidates’ experiences with gender and sexuality in the classroom, offering insight and strategies to better prepare teachers and teacher educators to support LGBTQ youth and families. This volume addresses the need for broader, more in-depth qualitative data describing teacher candidates’ responses to diversity in the classroom (including gender, sexuality, race, class and religion). By using pedagogical tools such as narrative writing and positioning theory, teacher candidates explore these issues to better understand their own students’ narratives in deeply embodied ways. This book calls for schools to be places where oppression, in all its complexity, is explored and challenged rather than replicated.
Keywords: LGBTQIA2+; approches et analyses; discipline; formations; hétérosexisme; identités LGBTQIA2+; intersectionnalité; outils; outils didactiques; privilèges; pédagogie; religion; sciences de l'éducation; sexualité; systèmes d'oppressions; thématiques

Whose Culture Has Capital? A Critical Race Theory Discussion of Community Cultural Wealth - Yosso, Tara J. (Race, Ethnicity and Education, 2005)
This article conceptualizes community cultural wealth as a critical race theory (CRT) challenge to traditional interpretations of cultural capital. CRT shifts the research lens away from a deficit view of Communities of Color as places full of cultural poverty disadvantages, and instead focuses on and learns from the array of cultural knowledge, skills, abilities and contacts possessed by socially marginalized groups that often go unrecognized and unacknowledged. Various forms of capital nurtured through cultural wealth include aspirational, navigational, social, linguistic, familial and resistant capital. These forms of capital draw on the knowledges Students of Color bring with them from their homes and communities into the classroom. This CRT approach to education involves a commitment to develop schools that acknowledge the multiple strengths of Communities of Color in order to serve a larger purpose of struggle toward social and racial justice.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; sciences de l'éducation; sex2283; thématiques; théorie critique de la race